2012
DOI: 10.1186/1477-5751-11-13
|View full text |Cite
|
Sign up to set email alerts
|

No effect of 6-month intake of glucosamine sulfate on Modic changes or high intensity zones in the lumbar spine: sub-group analysis of a randomized controlled trial

Abstract: BackgroundThe underlying pathology and natural course of Modic changes (MC) in the vertebral body marrow and high intensity zones (HIZs) in the annulus fibrosus is not completely clarified. These findings on magnetic resonance imaging (MRI) have initiated different treatments with little or unclear effect. In a randomized trial (n = 250), glucosamine sulfate (GS) had no effect on low back pain related disability. GS could still have an effect on MC and HIZ. In this sub-study, 45 patients from the trial who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
1
11
0
1
Order By: Relevance
“…Such data were included in articles on spondylarthritis (1)(2)(3)(4)(5), fractures (6), Modic changes (MCs) (7), hemangiomas (8), and pedicle screw loosening (9). However, all but one (6) of these reliability studies had only two observers, most (1,3-5,7-9) had small patient samples (n ¼ [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], only one (8) included measurements (of signal intensities); the spondylarthritis studies were limited to lesion detection (1)(2)(3)(4)(5). Reliability estimates differed widely in these heterogeneous studies where radiologists and non-radiologists interpreted various fat-suppressed 1.5-T or 3-T series.…”
Section: Introductionmentioning
confidence: 99%
“…Such data were included in articles on spondylarthritis (1)(2)(3)(4)(5), fractures (6), Modic changes (MCs) (7), hemangiomas (8), and pedicle screw loosening (9). However, all but one (6) of these reliability studies had only two observers, most (1,3-5,7-9) had small patient samples (n ¼ [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], only one (8) included measurements (of signal intensities); the spondylarthritis studies were limited to lesion detection (1)(2)(3)(4)(5). Reliability estimates differed widely in these heterogeneous studies where radiologists and non-radiologists interpreted various fat-suppressed 1.5-T or 3-T series.…”
Section: Introductionmentioning
confidence: 99%
“…This mater raises the question that whether bioavailability of GlcN form different formulations is responsible for the discrepancy between the outcomes of various clinical trials, or patients are underdosed when treated with the common 1500 mg/day regimen. Surprisingly, after many clinical trials, which reported no or marginal effects for 1500 mg/day GlcN in OA, the subsequent studies [15][16][17][18][19] still have used the same regimen with no attempt to try a greater daily dose. To the best of our knowledge, no information is available as to the GlcN minimum effective dose or concentration in animals or human.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the discs have no free surface in contact with synovial fluid and when small molecules such as GL are injected intravenously into the blood stream, they diffuse from blood vessels at the endplates and outer annulus periphery into discs with the transport being affected by pathological alterations to these pathways. Nevertheless, there is some interest in use of GL for treatment of back pain and disc degeneration [23,24].…”
Section: Introductionmentioning
confidence: 99%